Analysis of Student Misconceptions in the Implementation of Counseling Guidance Services in Schools - Sawal Mahaly; Emma Rumahlewang (Jurnal Ilmiah Pendidikan Holistik (JIPH), 2022)
This study aims to identify students' misunderstandings in the implementation of guidance and counseling services in schools. The sample in the research was 64 students at SMP Negeri 94 Central Maluku. The method of determining the sample using saturated sampling. Based on the results of the study, it was revealed that there were still student misunderstandings about the implementation of guidance and counseling services, including; first, guidance counseling is limited to certain students with a presentation of 75% in the High category, secondly, guidance counseling teachers/school counselors are school police with a presentation of 75% in the High category, third, the success of guidance and counseling services depends on facilities and infrastructure with a presentation of 73.44% in the High category, the four guidance and counseling only complement educational activities with a presentation of 71.88% in the High category, and the fifth guidance and counseling is considered as a mere process of giving advice with a presentation of 70.31% in the High category.